Assesing social vulnerability to flooding in Metro Manila using principal component analysis - See, Justin Charles G. (Philippine Sociological Review, 2015)
Earlier works measuring social vulnerability to flooding in cities focused mainly on biophysical, socio-demographic, or structural components of the hazard. Most of them are either: general, focusing on the city as a whole or specific, focusing on a particular district or community. These studies highlight the need to expand the concept of social vulnerability by examining the socio-economic and political dimensions of urban vulnerability at both city and community levels through quantitative methodologies. This paper argues that the socio-economic and political components of urban vulnerability tend to interact with the biophysical dimensions of flooding and tend to magnify/intensify its effects on the city and its residents, especially the poor residing along river lines. Using principal component analysis (PCA), this study measured the social vulnerability index of seventeen Metro Manila cities/ municipality based on the 2010 census data and a sample of flood prone communities drawn from the three flood basins of the metropolis. Results show that the components of social vulnerability vary across the city, barangay, and household levels, highlighting the multidimensionality and heterogeneity of social vulnerability across different local contexts. The expanded analysis also revealed that social capital and access to basic services are significant components of social vulnerability and adaptive capacities at the household level.